"Intriguing Ideas, Plotting Bögen": Thinking the Limit of Allegory in Walter Benjamin's Trauerspielbuch. Issue 2 (2nd April 2016) - Rosenbrück, Jonas
Abstract : Although Walter Benjamin's interest in mathematics is well known, its specific relationship with other parts of his thought often remains unexplored. This article proposes a reading of Benjamin's "Ursprung des deutschen Trauerspiels" that focuses on the figure of the Bogen as both mathematical and literary figure, illuminating Benjamin's conceptions of allegory and language. The central, yet often obscure, role of intrigue—of the plotter—in the Trauerspiel is read in the context of the plotting of a curve toward redemption; from the arc of allegory arises a thinking of the highly contorted space of the Trauerspiel and of an allegorizability before and beyond subjectivity, a thinking that finds an analogue in the mathematics of Benjamin's time and that echoes his early interest in another type of Bogen, the rainbow ( Regen-bogen ). This space of the Bogen opens onto an ethics of the middle of "Mitteilbarkeit."